2020
DOI: 10.1016/j.psj.2020.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Thermal processing of corn and physical form of broiler diets

Abstract: This study aimed to assess the effect of preprocessing of corn and of physical form of diets on growth performance, carcass yield, and nutrient digestibility in broilers and also the influence of corn processing on pellet quality. A total of 1,080 male Cobb chicks from 1 to 35 D were evaluated. Birds were distributed according to a completely randomized design in a 3 × 2 factorial arrangement, with 3 types of corn processing (unprocessed, pelleted, or expanded), and 2 diet physical forms (mash or pelleted), to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Similarly, Rezaeipour and Gazani [ 32 ] found that different feed particle sizes did not affect the breast and thigh relative weights. Also, Massuquetto et al [ 33 ] reported that carcass yield, breast, thigh, and drumstick yields were not affected by the physical form of diet. Interestingly, the present work showed that finely ground corn grain inclusion in the broiler diet significantly decreased the abdominal fat pad in comparison to those fed diets containing coarsely ground corn.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Rezaeipour and Gazani [ 32 ] found that different feed particle sizes did not affect the breast and thigh relative weights. Also, Massuquetto et al [ 33 ] reported that carcass yield, breast, thigh, and drumstick yields were not affected by the physical form of diet. Interestingly, the present work showed that finely ground corn grain inclusion in the broiler diet significantly decreased the abdominal fat pad in comparison to those fed diets containing coarsely ground corn.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of carbohydrase enzymes in corn-soy-based diets for broiler is still unclear (Rabello et al 2021). Massuquetto et al (2020) applied 84 C for 13 s for corn conditioning and 105 C for corn expansion. They found that DM digestibility increased in both processing methods compared with non-processed corn, which contradicts the results of this experiment.…”
Section: Nutrient Utilisationmentioning
confidence: 99%
“…Pelleting is the most common form of heat processing in broilers feed production (Massuquetto et al 2020). Many benefits that can be attributed to feed pelleting include improving nutrient availability, destroying inhibitors and toxins, facilitating the use of a wide range of raw materials in diet formulations, producing hygienic diet, and reducing feed wastage.…”
Section: Introductionmentioning
confidence: 99%